Coronavirus Disease 2019 Coexistence in the Daily Practice - Tallarico, Marco; Cicciù, Marco; Lumbau, Aurea Immacolata; Meloni, Silvio Mario (European Journal of Dentistry, 2020)
The purpose of the present narrative review was to evaluate and discuss the actual available information regarding coronavirus disease 2019 and dental practice, and to share recommendations with the intent to help dentists in providing a safe and healthful workplace during pandemic. A step-by-step workflow is presented including prevention and measures to reduce risk for cross infections before, during, and after the dental treatments. Individualization of different risk-level zones and the establishment of a team-based chain control is also presented. The present manuscript may offer deeper knowledge and discussion regarding recommended procedures aimed to reduce risk for dental health care workers contamination and cross infections. Within these, infection prevention in dental settings, respect of general rules, containment measures, proper use of the personal protective equipments (PPE), and well-organized chain control of all the staff, with definition of risk zones and specific responsibility could be an adjunctive but important step to control the spread of the disease.
Keywords: COVID-19; Public Health Dentistry; Infection control, dental; Primary prevention